Ursula Rothe, The Toga and the Roman identity, London–New York, Bloomsbury Academic, 2020, ix, 241 pp. [ISBN: 978-1-4725-7154-0]. - Gómez García, Natalia (Gerión. Revista de Historia Antigua, 2021)
Reseña de la obra de Ursula Rothe, The Toga and the Roman identity, London–New York, Bloomsbury Academic, 2020, ix, 241 pp. [ISBN: 978-1-4725-7154-0].